2009
DOI: 10.1097/aln.0b013e3181a4c706
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sevoflurane and Propofol on the Nociceptive Withdrawal Reflex and on the H Reflex

Abstract: Probably because of the polysynaptic relay, the attenuation of the withdrawal reflex exceeds the attenuation of the H reflex. Sevoflurane produces a larger inhibitory effect on the H reflex than propofol, which confirms that the ventral horn is a more important target for volatile anesthetics, whereas effects of propofol on this site of action are rather limited. Our findings indirectly suggest for propofol a relatively stronger effect within the dorsal horn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 52 publications
1
22
1
Order By: Relevance
“…The first component, the nociceptive flexion reflex, allows a highly specific and sensitive assessment of spinal nociception in awake subjects 11 and in subjects under general anaesthesia. 25,26 It constitutes an experimental means of standardising the paradigm of 'movement responses evoked by noxious stimulation', which is the current gold standard for the measurement of acute pain in animals, 27,28 and in unconscious or anaesthetised humans. 29 Applicability of the nociceptive flexion reflex has been demonstrated for a wide range of different anaesthetic regimes.…”
Section: Discussionmentioning
confidence: 99%
“…The first component, the nociceptive flexion reflex, allows a highly specific and sensitive assessment of spinal nociception in awake subjects 11 and in subjects under general anaesthesia. 25,26 It constitutes an experimental means of standardising the paradigm of 'movement responses evoked by noxious stimulation', which is the current gold standard for the measurement of acute pain in animals, 27,28 and in unconscious or anaesthetised humans. 29 Applicability of the nociceptive flexion reflex has been demonstrated for a wide range of different anaesthetic regimes.…”
Section: Discussionmentioning
confidence: 99%
“…In a study investigating the influence of different anaesthetics on hind paw withdrawal in rats the effect of propofol on nociception appeared to outlast the duration of general anaesthesia (O’Connor & Abram 1995). Another study comparing the effects of propofol and sevoflurane on the nociceptive withdrawal reflex concluded that propofol exerts a relatively stronger effect on dorsal horn nociceptive processing than does sevoflurane (Baars et al. 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent evidence suggests that the volatile agent sevoflurane has a greater effect than propofol on the motor neurons of the anterior horn. 29 A second critical difference between the studies centers on the stimulation protocol used in each to elicit tceMEPs. In the current study, the average stimulating voltage was 525 V, delivered using a commercially available constant voltage stimulator.…”
Section: Discussionmentioning
confidence: 99%